Kegiatan Berbicara Di Depan Umum Pada Yayasan Mandiri Citra Mentawai - Gusnayetti, Gusnayetti; Handrina, Emi; Saputra, David (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
The development and application of science and technology, which is a higher education academic activity and a form of community service, is more focused on efforts to solve problems faced by society and improve the quality of human resources. Community service by the Imam Bonjol Padang College of Social and Political Sciences is the practice of science and technology carried out institutionally through scientific methods directly to communities who need it in an effort to make development a success. Direct practice means conveying the science and technology to be applied, disseminated or demonstrated directly to the target community outside the campus. The community service method is carried out in relation to determining schedules, dividing tasks, determining the number of participants and extension materials, so various meetings are held to discuss and exchange ideas among members implementing the extension. These meetings aim to determine plans and receive input related to the extension activities that will be carried out. , Public speaking requires certain techniques. The speaker must be able to attract the audience's attention so that they continue to listen to what he is saying. Regardless of whether the scope of the situation is official or not, before appearing in public, the speaker must prepare and ensure several supporting things in advance so that the speaking activity runs smoothly. Things that need to be prepared can come from internally to the speaker or from externally. Public speaking can take the form of scientific presentations, seminars, speeches or scientific orations, debates, and so on.